SIRT1 is a regulator of autophagy: Implications in gastric cancer progression and treatment. Issue 16 (3rd June 2015) - Qiu, Guanglin; Li, Xuqi; Che, Xiangming; Wei, Chao; He, Shicai; Lu, Jing; Jia, Zongliang; Pang, Ke; Fan, Lin
Abstract : Silent mating type information regulation 1 (SIRT1) is implicated in tumorigenesis through its effect on autophagy. In gastric cancer (GC), SIRT1 is a marker for prognosis and is involved in cell invasion, proliferation, epithelial‐mesenchymal transition (EMT) and drug resistance. Autophagy can function as a cell‐survival mechanism or lead to cell death during the genesis and treatment of GC. This functionality is determined by factors including the stage of the tumor, cellular context and stress levels. Interestingly, SIRT1 can regulate autophagy through the deacetylation of autophagy‐related genes (ATGs) and mediators of autophagy. Taken together, these findings support the need for continued research efforts to understand the mechanisms mediating the development of gastric cancer and unveil new strategies to eradicate this disease.